Multi-element, multi-compound isotope profiling as a means to distinguish the geographical and varietal origin of fermented cocoa (Theobroma cacao L.) beans. (1st December 2015) - Diomande, Didier; Antheaume, Ingrid; Leroux, Maël; Lalande, Julie; Balayssac, Stéphane; Remaud, Gérald S.; Tea, Illa
Highlights: 13 C and 15 N analysis on different sub-matrices of fermented cocoa beans is proposed. 15 N content is useful for continental origin distinction of cocoa. 13 C and 15 N allow the separation of local origins of cocoa in Ivory Coast. Abstract: Multi-element stable isotope ratios have been assessed as a means to distinguish between fermented cocoa beans from different geographical and varietal origins. Isotope ratios and percentage composition for C and N were measured in different tissues (cotyledons, shells) and extracts (pure theobromine, defatted cocoa solids, protein, lipids) obtained from fermented cocoa bean samples. Sixty-one samples from 24 different geographical origins covering all four continental areas producing cocoa were analyzed. Treatment of the data with unsupervised (Principal Component Analysis) and supervised (Partial Least Squares Discriminant Analysis) multiparametric statistical methods allowed the cocoa beans from different origins to be distinguished. The most discriminant variables identified as responsible for geographical and varietal differences were the δ 15 N and δ 13 C values of cocoa beans and some extracts and tissues. It can be shown that the isotope ratios are correlated with the altitude and precipitation conditions found in the different cocoa-growing regions.